Efektivitas Penyidikan Tindak Pidana Dalam Undang-Undang Tentang Informasi Dan Transaksi Elektronik Terkait Phishing Di Wilayah Hukum Kepolisian Daerah Riau - Ihsan Riznawara; Syaifullah Yophi Ardianto; Riyanda Elsera Yozani (Peneliti.net, 2026)
The rapid advancement of technology has become an inseparable part of human life. On one hand, this progress brings numerous benefits to daily activities; on the other hand, it also opens opportunities for criminal acts. One prevalent crime is phishing, which aims to obtain victims' electronic information, particularly related to financial data. This information is then used to unlawfully access and take the victim's funds without their consent. This research is a sociological study based on social realities to uncover the facts on the ground and answer the research problems. The study was conducted in the jurisdiction of the Riau Regional Police. The population and sample include parties who are directly related to the issues being investigated. The sources of data used in this research consist of primary, secondary, and tertiary data. Data collection techniques include interviews, questionnaires, and literature review. The results of the study indicate that the investigation of criminal acts under the Law on Electronic Information and Transactions (ITE Law) related to phishing within the jurisdiction of the Riau Regional Police has not been running optimally. This is evident from the relatively low number of resolved cases. The investigation process begins with examining the victim, collecting evidence that can identify the perpetrator, and establishing cooperation with stakeholders. Once all procedures are properly carried out, the suspect is named and the case is submitted to the Prosecutor’s Office. The obstacles faced during the investigation include limited human resources and supporting technology within the police force, difficulties in identifying perpetrators operating in an organized manner, challenges in tracking the bank accounts used by the perpetrators, and low public awareness levels. To overcome these obstacles, the Riau Regional Police have made efforts to enhance human resources and technological infrastructure, collaborate with stakeholders such as banks, other regional police departments, the National Police Headquarters, and social media platforms, as well as conduct public education and outreach programs.Repressive measures involve investigation and prosecution.The main challenges in law enforcement are limited human resources and facilities, difficulties in identifying and tracking perpetrators who operate in an organized manner, and low public awareness. To overcome these obstacles, the Riau Regional Police have taken steps such as improving personnel capacity and resources, cooperating with stakeholders including banks, other regional police departments, the National Police Headquarters, and social media platforms, as well as providing continuous public education and outreach.